Meningkatkan Kerjasama Siswa Melalui Metode Snowball Throwing dalam Materi Pembelajaran Unsur Pendukung Tari Kelas X MIPA 4 SMA Negeri 2 Depok Tahun 2023 - Joki ramadhan Goloa, Agustiningsih Pratami Goloa; Rahmida Setiawati; Nursilah (Program Studi Pendidikan Tari FBS UNJ, 2023)
This research raised the problem that exists in the students of class X MIPA 4 in State High School 2 Depok, which is the lack of cooperation in the way of learning. This problem occurs because the media and methods of learning in schools have not yet led to activities that require cooperation, learning that is monotonous makes students bored. This study aims to improve student cooperation in the way and process of learning using the method of learning snowball throwing in the material of supporting dance elements, which is beneficial to enhancing the ability of students to cooperate. This study uses the method of Class Action Research (PTK) by separating the action intervention design of Kurt Lewin, which consists of two cycles and each cycle has four stages, namely planning (Planning), action (Action), observation (Observing), and reflection. (Reflecting). The research took place from February to May 2023 at State High School 2 Depok, West Java. Data is collected through the learning process in the dance support element material over 4 meetings over 2 cycles. The data collection techniques used in this study are lifting, observation, and interviews. The results of the research showed that the application of the method of learning snowball throwing in the dance supporting element material can improve student cooperation based on the results at pre-cycle 40%, increasing at cycle I to 75%, and at cycle II to 94%. The results indicated that the method of learning snowball throwing could significantly enhance student collaboration. The conclusion of this study is that the method of learning snowball throwing can be beneficial and can be a way of learning for all students, especially to enhance cooperation. This is because the method of learning snowball throwing has experienced a significant improvement, as demonstrated by the learning results using dance supporting elements.